PENGARUH JUMLAH PENDUDUK DAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP PENGANGGURAN DI KOTA MOJOKERTO - ABDUL MANAP (Universitas Negeri Surabaya, 2013)
High unemployment is one of the few obstacles to development in almost all regions, so it’s interesting to assessed, considering this problem also potentially lead to poverty. Mojokerto is one of the regions that currently trying to reduce the amount of unemployment as few as possible. There are several factors that cause high unemployment such as Gross Domestic Product and population explosion in Mojokerto. The purpose of this study was to analyze the effect of population and Gross Domestic Regional Product on unemployment in Mojokerto. The type of this research is quantitative using associative approach. The data used on this research are time series data (periodic) in 2001 – 2011. The research variables are population and Gross Domestic Product as an independent variable and unemployment as the dependent variable. Hypothesis testing is performed by multiple linear regression analysis, which first tested the classical assumptions. Results of this research proved that partially or simultaneously population and Gross Domestic Regional Product significantly affect on unemployment in Mojokerto. The coefficient of determination (R2) by 57 percent, while the remaining 43 percent is explained by other variables not included in the research. Keywords: Unemployment, Gross Domestic Regional Product (GDRP), and Population